PENDIDIKAN DAN PELATIHAN DALAM MENINGKATKAN MODEL KERJASAMA USAHA MENENGAH KECIL DAN MIKRO DENGAN USAHA BESAR DI KECAMATAN CIKONENG KABUPATEN CIAMIS - Elin Herlina (Universitas Galuh, 2014)
This article direct to describe of training and education for overcome corporate small-Midle enterprises and big enterprises models at Cikoneng District. The necesary of training and education will increasing of common purpose, aim, and value of company achievment. During the last research to find structure of problems by typology and characteristic of organization culture and production factors in single model co-operate small-Midle enterprises and big enterprises, the result has find another leverage factor overview training and education. To a comprehensive result by approach input, process, and output and finded by description approach through case study strategic describe to this article. The result of co- operate by sub-contract way based on common mutual, common strange, common benefit as direct as Act Number 20/2008 (small-midle enterprises) we need training and education to input this model. Recommendation in this article not only use to optimalization supply row materials, finish production, market strategic, and minimazing over head cost by co-operate small-Midle enterprises and big enterprises benefits but training and education will over come corporate small-Midle enterprises and big enterprises models at Cikoneng District .